Determinants of credit risk of Indonesian Sharīʿah rural banks - Unggul Priyadi; Kurnia Dwi Sari Utami; Rifqi Muhammad; Peni Nugraheni (ISRA International Journal of Islamic Finance, 2021)
Purpose - This study aims to examine the influence of internal and external factors on the credit risk (represented by nonperforming financing [NPF]) of Indonesian Sharīʿah rural banks (SRBs) - a type of Islamic bank that provides Islamic financial services especially to small and medium businesses in Indonesia. Internal variables comprise capital adequacy ratio (CAR), financing to deposit ratio (FDR), return on assets (ROA), operating expense ratio (OER), financing to value (FTV) and profit and loss sharing (PLS) financing ratio. External variables comprise inflation, economic growth and interest rate. Design/methodology/approach - The study uses the annual reports of SRBs in Indonesia as secondary data for the years 2010-2019. Auto regressive distributed lag (ARDL) is used as the analysis method to examine the short-run and long-run relationships between the variables. Findings - The findings indicate that four variables experienced a lag in the short run, namely, NPF, inflation, CAR and PLS, with different results recorded for each of the variables. Furthermore, the long-run results show that CAR and ROA influence the NPF of SRBs positively, whereas inflation and PLS have a negative influence on NPF. The rest of the variables - notably economic growth, interest rate, FDR, FTV and OER - do not have an influence on NPF in SRBs. Research limitations/implications - The level of NPF in SRBs exceeds the provision of the Central Bank of Indonesia. The findings are expected to have implications for SRBs and the regulator to consider and to manage the factors related to NPF properly due to the important role of SRBs in small and medium businesses' development. Originality/value - This study measures the determinants of NPF using internal and external variables, including the addition of a dummy variable, notably FTV. This study also uses ARDL to analyze the financial policies involving data at the present time and lagged time.
Keywords: 330; ARDL; Credit risk; Internal factors; External factors; Non-performing financing; Sharīʿah rural banks